1990
DOI: 10.1063/1.344983
|View full text |Cite
|
Sign up to set email alerts
|

Particulate generation in silane/ammonia rf discharges

Abstract: The rate of particle generation in a SiH4/NH3 rf discharge has been studied as a function of the discharge operating parameter space, electrode geometry, and power supply coupling mode. Measurements of the bulk quantity of particles produced in the discharge reveal that the mode of coupling (capacitive or dc) as well as the electrode temperature significantly affects particle generation rates. Laser light scattering measurements made as a function of the plasma power density indicate that particle generation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Process-induced particles often grow by a cluster interaction or coagulation process [15], followed by a more open agglomeration of primary particles [16]. Coagulation and agglomeration are the processes which make possible the very rapid growth of particles to sizes visible by LLS noted in this study.…”
Section: Dynamic Laser Light Scattering In the Unm Reference Cellmentioning
confidence: 77%
See 1 more Smart Citation
“…Process-induced particles often grow by a cluster interaction or coagulation process [15], followed by a more open agglomeration of primary particles [16]. Coagulation and agglomeration are the processes which make possible the very rapid growth of particles to sizes visible by LLS noted in this study.…”
Section: Dynamic Laser Light Scattering In the Unm Reference Cellmentioning
confidence: 77%
“…4 from the particle trap region shows the trap is densely populated with particles. Numerous pervious studies [10,16] have shown particle densities under such conditions reach 10 6 /cm 3 to 10 8 /cm 3 .…”
Section: Dynamic Laser Light Scattering In the Unm Reference Cellmentioning
confidence: 99%
“…The formation and growth process of negative ionic clusters is a widely studied topic, [5][6][7] and so is the formation of dust. [8][9][10][11][12][13][14] However, the formation of large positive silicon clusters is less known. In radio-frequency ͑rf͒ plasmas, their presence is not likely since they are not confined by the electric field.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11] However, these studies were based on single wafers and they described the motion of particle clouds, but they did not accurately reflect manufacturing conditions.…”
Section: Introductionmentioning
confidence: 99%